AquaNet - PARAFAC component parameters from Erken AquaNet platform, 2022-07-07–2022-08-12 - Erken Laboratory (Uppsala University, 2024)
Data contains PARAFAC components to describe dissolved organic matter composition (DOM) from grab samples taken from the AquaNet mesocosms.
Erken Laboratory (2024). AquaNet - PARAFAC component parameters from Erken AquaNet platform, 2022-07-07–2022-08-12 [Data set]. Swedish Infrastructure for Ecosystem Science (SITES). https://hdl.handle.net/11676.1/9J6Q6R2yRS8L1yEVocoHResc
Keywords: SITES AquaNet; Soil Science; Markvetenskap; Agriculture, Forestry and Fisheries; Jordbruk, skogsbruk och fiske; Agricultural Science; Jordbruksvetenskap; Ecology; Ekologi; Multidisciplinary Geosciences; Multidisciplinär geovetenskap; Environmental Sciences; Miljövetenskap; Climate Science; Klimatvetenskap